Evaluation of the Knowledge and Practices About Drug Prescribing and Adverse Reaction Reporting Among Turkish Dentists - Kıroğlu, Olcay; Khan, Zakir; Berktaş, Fatih; Öz, Emine; Ünal , İlker; Karatas, Yusuf (European Journal of Therapeutics, 2023)
Introduction: The purpose of this study was to assess dental care professionals' drug prescription knowledge, practices, and reporting of adverse drug reactions (ADRs). Methods: A cross-sectional exploratory study was conducted by using a face-to-face survey administered to a sample of dentists from tertiary care hospitals in Adana, Türkiye. A questionnaire consisted of six sections with closed-ended items including sociodemographic characteristics, knowledge about drugs, patient history information, counseling practices during prescribing, source of information and ADR reporting. Results: The study included 180 dentists, with a 95.3% response rate. More than half of the dentists (50.6%) stated their level of knowledge about drug price/cost as low. Most of the dentists (50.6%;n=91) claimed that they never/rarely asked about health insurance during patient history information. Moreover, most of the participants reported that they never/rarely and sometimes counsel the patients regarding drug mechanism of action, side effects of the drug, interaction of prescribed drug with other drugs/nutrients. It was determined that the dentists learned about the drugs from Vademecum (Turkish Medication Guidebook: 70%;n=126) and the internet (55%;n=99). A higher proportion (85.5%) of the dentists indicated that they did not report ADR during their clinical practice. Conclusion: This study showed a general improvement in dentists prescribing knowledge and practices, although they reported some lack of knowledge regarding drug cost, discussion about the possible side effect of a drug/interaction with other drugs/nutrients with patients and under-reporting of ADRs. Periodic education and training for dentists are critical to overcoming any problem related to prescribing errors and potential ADRs.